Composite microsphere as well as preparation method and application thereof

By using a composite microsphere structure in the negative electrode sheet of a lithium-ion battery, the core contains cyclosiloxane and a low-boiling point solvent, and the outer shell is made of a thermoplastic polymer. This solves the problem of side reactions between the negative electrode material and the electrolyte, and realizes the control of the battery core. Effective suppression of thermal runaway and balance of power performance.

CN119361699APending Publication Date: 2025-01-24CHONGQING CHANGAN AUTOMOBILE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411478017.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art cannot improve the intrinsic side reaction characteristics of the negative electrode material of lithium-ion battery and the electrolyte, which makes it difficult to solve the problem of thermal runaway.

Method used

The composite micro -ball structure is adopted. The kernel contains the cyclosicoxane as a safe improvement agent and a low -boiling point solvent. The shell is prepared by the thermoplastic polymer monomer and the linked agent. Chemical reactions of negative electrodes and electrolytes.

Benefits of technology

Effectively suppress the heat of the battery cells, take into account the safety performance and power performance, and solve the problem of the side reaction of negative materials and electrolytes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361699A_ABST
    Figure CN119361699A_ABST
Patent Text Reader

Abstract

The invention relates to a composite microsphere and a preparation method and application thereof, and relates to the technical field of materials and electrochemistry, the composite microsphere comprises an inner core and a shell, the inner core comprises a safety improver and a low-boiling-point solvent with the boiling point not higher than 105 DEG C, the shell is prepared from a thermoplastic polymer monomer and a cross-linking agent, and the safety improver is cyclosiloxane. The composite microsphere disclosed by the invention is kept stable under a conventional working condition; when mechanical short-circuit heat production or external heating occurs, the low-boiling-point solvent expands to cause polymer shell breakage, the safety improver is released to perform ring-opening polymerization and cover the damaged part of a negative electrode SEI film, chemical side reaction heat production of a negative electrode and electrolyte is blocked, and the possibility that a battery cell enters a self-heat-production chain reaction is reduced, so that thermal runaway of the battery cell is effectively inhibited, and the service life of the battery cell is prolonged. The battery cell has safety performance and power performance at the same time, and the problem that the intrinsic side reaction characteristics of the negative electrode material and the electrolyte cannot be improved in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of materials and electrochemical technology, and in particular to a composite microsphere and a preparation method and application thereof. Background Art

[0002] With the rapid development of the new energy vehicle industry, higher requirements have been put forward for the energy density and safety of lithium-ion power batteries. However, the safety of lithium-ion power batteries with high specific energy material systems currently on the market, such as high nickel ternary-graphite and high nickel ternary-silicon / graphite material systems, is weaker than that of lithium iron phosphate-graphite material system batteries, which has brought adverse effects on the development of the industry. Due to the development needs of pure electric new energy vehicles with lower operating costs, the safety needs of high energy density lithium-ion batteries are more urgent.

[0003] In the related art, the safety of battery negative electrode materials is improved mainly by coating the surface of the electrode with materials that inhibit thermal runaway. For example, a lithium-ion battery silicon-carbon negative electrode and its preparation method, by coating the temperature-sensitive conductive material on the surface of the current collector, the temperature-sensitive conductive coating can quickly increase the impedance of the negative electrode when the temperature rises to a certain level, preventing the lithium-ion battery from thermal runaway due to abuse such as puncture, overcharging, short circuit, etc., so as to improve the thermal safety performance of the silicon negative electrode.

[0004] Although the above safety coating method can avoid triggering thermal runaway to a certain extent and improve the passability of mechanical abuse tests, it cannot improve the intrinsic side reaction characteristics of the negative electrode material and the electrolyte. Once thermal runaway is triggered, the negative electrode will still react violently with the electrolyte, causing the battery cell to self-generate heat and trigger thermal runaway. Summary of the invention

[0005] The present application provides a composite microsphere and a preparation method and application thereof, so as to solve the problem in the related art that the intrinsic side reaction characteristics of the negative electrode material and the electrolyte cannot be improved.

[0006] In a first aspect, the present application provides a composite microsphere comprising a core and a shell, wherein the core comprises a safety improver and a low-boiling-point solvent having a boiling point not higher than 105° C., and the shell is prepared from a thermoplastic polymer monomer and a cross-linking agent;

[0007] The above safety improving agent is cyclosiloxane.

[0008] In some embodiments, the safety improver includes at least one of 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetra(3,3,3-trifluoropropyl)cyclotetrasiloxane, octamethylcyclotetrasiloxane, 2,2,4,4,6,6-hexamethylcyclotrisiloxane, and 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane.

[0009] In some embodiments, the low boiling point solvent includes at least one of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,1,2,3,3-hexafluoro-3-(2,2,3,3-tetrafluoropropoxy)propane, 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether, and 1,1,2,3,3,3-pentafluoropropyl-2,2,2-trifluoroethyl ether.

[0010] In some embodiments, the thermoplastic polymer monomer includes at least one of acrylonitrile, methyl methacrylate, methacrylic acid, methyl acrylate, butyl acrylate, vinyl acetate, and halogenated olefins.

[0011] In some embodiments, the thermoplastic polymer monomers include methyl acrylate and other monomers;

[0012] The mass of the methyl acrylate is not less than 60% of the total mass of the thermoplastic polymer monomer;

[0013] The other monomer is one of acrylonitrile, methyl methacrylate, methacrylic acid, butyl acrylate, vinyl acetate and halogenated olefin.

[0014] In some embodiments, the cross-linking agent is 1,4-butanediol dimethyl acrylate or polydipentaerythritol hexaacrylate; the mass of the cross-linking agent is 0.05-1% of the mass of the thermoplastic polymer monomer.

[0015] In some embodiments, the ratio of the sum of the mass of the safety improver and the low boiling point solvent to the mass of the thermoplastic polymer monomer is (0.78-2.7):1; the ratio of the sum of the mass of the safety improver to the mass of the low boiling point solvent and the thermoplastic polymer monomer is 1:(3-4).

[0016] In some embodiments, the average particle size Dv(50) of the composite microspheres is between 5 μm and 30 μm.

[0017] In a second aspect, the present application provides a method for preparing the above-mentioned composite microspheres, comprising the following steps:

[0018] Thermoplastic polymer monomers, initiators, crosslinking agents, safety improvers and low boiling point solvents are mixed and stirred to obtain an oil phase solution;

[0019] Deionized water, a dispersant, sodium chloride, trisodium citrate and ethanol are mixed and stirred to obtain an aqueous phase solution;

[0020] The aqueous phase solution and the oil phase solution are mixed and stirred to form uniform micron-sized droplets of the oil phase dispersed in the aqueous phase to obtain a suspension;

[0021] The suspension is subjected to a cross-linking reaction under mechanical stirring and heating conditions to obtain a mixture;

[0022] After the mixture is cooled to room temperature, it is separated, washed and low-temperature dried to obtain the composite microspheres.

[0023] In a third aspect, the present application provides an application of the above-mentioned composite microspheres in a negative electrode plate of a battery.

[0024] Compared with the prior art, this application has at least the following beneficial effects:

[0025] The composite microsphere of the present application has a shell prepared from a thermoplastic polymer monomer and a crosslinking agent, and a core including a safety improver and a low-boiling-point solvent; under normal working conditions, the composite microsphere remains stable; when a mechanical short circuit generates heat or external heat is applied, the low-boiling-point solvent expands, causing the polymer shell to rupture, releasing the safety improver; the safety improver is a cyclosiloxane, which can be inserted into the lithium-embedded carbon Li x C 6 During catalysis, it undergoes ring-opening polymerization and covers the damaged parts of the negative electrode SEI film to block the heat generated by the chemical side reactions between the negative electrode and the electrolyte, reducing the possibility of the battery cell entering a self-heating chain reaction, thereby effectively suppressing the occurrence of thermal runaway of the battery cell, allowing the battery cell to take into account both safety performance and power performance, and solving the problem in related technologies that the intrinsic side reaction characteristics of the negative electrode material and the electrolyte cannot be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0027] Figure 1 This is a flow chart of the method for preparing composite microspheres provided in an embodiment of the present application. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present application clearer, the technical solution of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0029] The present invention provides a composite microsphere which remains stable under normal working conditions; when a mechanical short circuit generates heat or external heat is applied, the low boiling point solvent expands, causing the polymer shell to rupture, releasing a safety improver; the safety improver is a cyclosiloxane, which can be inserted into the lithium carbon Li x C 6 The negative electrode SEI film is covered by ring-opening polymerization under catalysis to block the heat generated by the chemical side reactions between the negative electrode and the electrolyte, reduce the possibility of the battery cell entering a self-heating chain reaction, and effectively inhibit the occurrence of thermal runaway of the battery cell, so that the battery cell can take into account both safety performance and power performance.

[0030] The composite microsphere provided in the present application comprises a core and a shell. The core comprises a safety improver and a low boiling point solvent, and the shell is prepared from a thermoplastic polymer monomer and a crosslinking agent; the safety improver is cyclosiloxane, and the boiling point of the low boiling point solvent is not higher than 105°C.

[0031] The composite microspheres of this embodiment have a core-shell structure, the outer shell is a thermoplastic polymer prepared from a thermoplastic polymer monomer and a crosslinking agent, and the inner core contains cyclosiloxane as a safety improver and a low boiling point solvent, which can be added to the negative electrode plate as an additive to solve the problem that the intrinsic side reaction characteristics of the negative electrode material and the electrolyte cannot be improved in the related art. The composite microspheres have stable chemical properties, obvious safety improvement effects, and have the potential for large-scale application.

[0032] In some embodiments provided herein, the safety improver includes at least one of 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetra(3,3,3-trifluoropropyl)cyclotetrasiloxane, octamethylcyclotetrasiloxane, 2,2,4,4,6,6-hexamethylcyclotrisiloxane, and 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane.

[0033] Preferably, the safety improver is 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane or 2,4,6,8-tetramethyl-2,4,6,8-tetra(3,3,3-trifluoropropyl)cyclotetrasiloxane.

[0034] More preferably, the safety improving agent is 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane.

[0035] In this embodiment, cyclosiloxane can be used as an effective negative electrode safety improver because of its stable structure and the fact that it is not easy to self-polymerize when heated. x C 6 Under catalysis, the ring-opening polymerization covers the damaged parts of the SEI film, blocks the contact between the negative electrode and the electrolyte, reduces the heat generated by the reaction between the negative electrode and the electrolyte, and thus inhibits the chain heat generation reaction of the battery cell.

[0036] In some embodiments, the use of cyclosiloxane safety improver as an electrolyte additive can effectively inhibit the reaction between the fully charged negative electrode and the electrolyte, but it also greatly increases the negative electrode impedance, affecting the battery discharge power performance.

[0037] In some embodiments provided herein, the low boiling point solvent includes at least one of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,1,2,3,3-hexafluoro-3-(2,2,3,3-tetrafluoropropoxy)propane, 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether, and 1,1,2,3,3,3-pentafluoropropyl-2,2,2-trifluoroethyl ether.

[0038] In this embodiment, the low boiling point solvent can expand when heated to destroy the polymer shell layer, thereby effectively promoting the release of the safety improving agent.

[0039] Preferably, the low boiling point solvent includes 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether or 1,1,1,2,3,3-hexafluoro-3-(2,2,3,3-tetrafluoropropoxy)propane.

[0040] More preferably, the low boiling point solvent includes 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0041] In some embodiments provided in the present application, the thermoplastic polymer monomer includes at least one of acrylonitrile, methyl methacrylate, methacrylic acid, methyl acrylate, butyl acrylate, vinyl acetate, and halogenated olefins.

[0042] In this embodiment, the polymer outer shell layer softens and reduces its strength after being heated, and ruptures under the action of pressure to release the safety improving agent inside.

[0043] Preferably, the above-mentioned thermoplastic polymer monomers include methyl acrylate and other monomers.

[0044] The mass of the methyl acrylate is not less than 60% of the total mass of the thermoplastic polymer monomer; the other monomers are one of acrylonitrile, methyl methacrylate, methacrylic acid, butyl acrylate, vinyl acetate and halogenated olefins.

[0045] In this embodiment, when the methyl acrylate content is too low, the glass transition temperature of the thermoplastic polymer is high, and it needs to be at a higher temperature to break when heated, which is not conducive to the release of the safety improver, and thus cannot effectively suppress heat generation.

[0046] In some embodiments provided in the present application, the cross-linking agent is 1,4-butanediol dimethyl acrylate or polydipentaerythritol hexaacrylate.

[0047] In this embodiment, the cross-linking agent is a conventional multifunctional cross-linking agent. By adding the cross-linking agent, the strength of the outer shell layer can be improved to prevent the composite microspheres from breaking during the negative electrode processing.

[0048] Furthermore, the mass of the cross-linking agent is 0.05-1% of the mass of the thermoplastic polymer monomer.

[0049] In this embodiment, the amount of cross-linking agent needs to be controlled; if the cross-linking agent content is too low, the strength of the prepared shell is insufficient and it is easy to break during the battery cell manufacturing process, resulting in a decrease in the battery cell rate performance; if the cross-linking agent content is too high, the strength of the prepared shell is too high and it is not easy to break, which in turn leads to excessively high temperature for the release of the safety improvement additive.

[0050] Preferably, the crosslinking agent is 1,4-butanediol dimethyl acrylate.

[0051] In some embodiments provided herein, the ratio of the sum of the mass of the safety improver and the low boiling point solvent to the mass of the thermoplastic polymer monomer is (0.78-2.70): 1. The ratio of the sum of the mass of the safety improver to the mass of the low boiling point solvent and the thermoplastic polymer monomer is 1: (3-4).

[0052] In this embodiment, by controlling the mass ratio of the safety improver and the low boiling point solvent to the mass ratio of the thermoplastic polymer monomer, the thickness of the microsphere shell can be effectively controlled, thereby controlling the timing of the microsphere rupture to release the safety improver. By controlling the mass ratio of the safety improver to the mass ratio of the low boiling point solvent and the thermoplastic polymer monomer, the mixing and dispersion effect of the safety improver and the low boiling point solvent in the composite microsphere can be effectively improved.

[0053] Preferably, the ratio of the sum of the mass of the safety improver and the low boiling point solvent to the mass of the thermoplastic polymer monomer is 1.35:1; the ratio of the sum of the mass of the safety improver to the sum of the mass of the low boiling point solvent and the thermoplastic polymer monomer is 1:3.35.

[0054] In some embodiments provided in the present application, the average particle size Dv(50) of the composite microspheres is between 5 and 30 μm. Specifically, the average particle size Dv(50) of the composite microspheres can be 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, or 30 μm.

[0055] In some embodiments provided in the present application, the thickness of the shell is 1.0 to 2.5 μm.

[0056] In this embodiment, by controlling the thickness of the outer shell, the problem that the outer shell is not easy to break due to the outer shell thickness being too large, and the problem that the outer shell is easy to break in advance due to the outer shell thickness being too small can be effectively avoided.

[0057] like Figure 1 As shown, the present application provides an embodiment of a method for preparing the above-mentioned composite microspheres, the method comprising the following steps:

[0058] S1. The thermoplastic polymer monomer, initiator, crosslinking agent, safety improving agent and low boiling point solvent are mixed and stirred to obtain an oil phase solution;

[0059] S2. After mixing deionized water, dispersant, sodium chloride, trisodium citrate and ethanol, an aqueous solution is obtained;

[0060] S3. The aqueous phase solution and the oil phase solution are mixed and stirred to form uniform micron-sized droplets of the oil phase dispersed in the aqueous phase to obtain a suspension;

[0061] S4. The suspension is subjected to a cross-linking reaction under mechanical stirring and heating conditions to obtain a mixture;

[0062] S5. After cooling the mixture to room temperature, the mixture is separated, washed, and low-temperature dried to obtain the composite microspheres.

[0063] Optionally, the mixing and stirring can be performed by mechanical stirring.

[0064] In this embodiment, the heating temperature in the above step S4 is 50-65° C. Preferably, the heating temperature in the above step S4 is 60° C.

[0065] In this embodiment, the temperature of the low-temperature drying in the above step S5 is 40-60° C. Preferably, the temperature of the low-temperature drying in the above step S5 is 50° C.

[0066] In this embodiment, the initiator can be a conventional free radical polymerization initiator. Optionally, the initiator is azobisisobutyronitrile.

[0067] In this embodiment, the above dispersant can be a conventional suspension polymerization dispersant as long as the dispersing effect is satisfied. Optionally, the above dispersant is polyvinyl alcohol, hydroxypropyl methylcellulose, or methylcellulose.

[0068] The preparation method of this embodiment is applicable to the above-mentioned composite microspheres, and the prepared composite microspheres have the effect of improving negative electrode safety and can be used as negative electrode additives to take into account both safety and power performance.

[0069] The embodiment of the present application also provides an application of the above-mentioned composite microspheres in a negative electrode plate of a battery.

[0070] In this embodiment, the composite microspheres are added as additives to the negative electrode plate of the battery for use.

[0071] The composite microspheres of this embodiment are suitable for a variety of negative electrode materials, such as graphite negative electrode, hard carbon negative electrode, silicon-carbon negative electrode, silicon-oxygen negative electrode, lithium metal negative electrode, no negative electrode material, etc.

[0072] The above-mentioned composite microspheres do not react with the negative electrode under normal conditions and do not affect the battery power performance; when heated, they can release the internal cyclosiloxane safety improver, change the chemical composition of the surface of the negative electrode material, isolate the negative electrode from the electrolyte, and inhibit the self-heating reaction of the negative electrode and the electrolyte.

[0073] In this embodiment, the battery may be a lithium ion battery or other metal ion batteries, such as Na ion, Ca ion, K ion, Mg ion and other metal ion batteries.

[0074] In other embodiments, the above-mentioned battery can also be various batteries using different ions as anodes and cathodes, batteries with solid electrolytes (including batteries with two electrolytes, one at the anode and the other at the cathode), and batteries with liquid electrolytes (such as organic electrolytes, aqueous electrolytes at various pH values, liquid electrolytes based on ionic liquids, or liquid electrolytes including mixtures of the above-mentioned various components).

[0075] The technical solution provided in this application is described in detail below in conjunction with embodiments.

[0076] Since lithium-ion technology is currently popular and often used, several examples are provided in the context of lithium-ion batteries.

[0077] Embodiment 1:

[0078] First, 100 g of polymer monomer (80 g of methyl acrylate, 20 g of acrylonitrile), 2.15 g of initiator azobisisobutyronitrile, 0.2 g of crosslinker 1,4-butanediol dimethyl acrylate, 54 g of safety improver 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, and 81 g of low boiling point solvent 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether were added to a reaction kettle and mixed under mechanical stirring to obtain an oil phase;

[0079] Secondly, add 2000 mL of deionized water, 8 g of carboxypropyl cellulose, 16 g of sodium chloride, 10 g of citric acid, and 50 g of ethanol into another reaction kettle and stir to dissolve to obtain an aqueous phase;

[0080] Then, the oil phase was added to the water phase, and stirred at 30° C. and 1200 rpm for 30 min to mix uniformly to obtain a suspension.

[0081] Finally, the suspension was heated to 60°C at a rotation speed of 500 rpm for 6 hours; after the reaction, the suspension was cooled to room temperature, the product was filtered, separated and washed with water, and then the product was dried at 50°C to obtain composite microspheres.

[0082] The composite microspheres of Examples 2 to 6 were prepared in a similar manner to that of Example 1, except that the selected raw materials and amounts were different. The specific differences are described below and Table 1.

[0083] Example 2

[0084] In Example 2, except that 100 g of the polymer monomer is 100 g of methyl acrylate and the cross-linking agent is 0.05 g of 1,4-butanediol dimethyl acrylate, which are different from Example 1, the remaining steps and parameters are the same as those of Example 1.

[0085] Example 3

[0086] In Example 3, except that 100g of polymer monomer is 60g of methyl acrylate plus 40g of acrylonitrile, the amount of cross-linking agent is 1g, the safety improver is 2,4,6,8-tetramethyl-2,4,6,8-tetrakis(3,3,3-trifluoropropyl)cyclotetrasiloxane, and the low boiling point solvent is 1,1,1,2,3,3-hexafluoro-3-(2,2,3,3-tetrafluoropropoxy)propane, which is different from Example 1, the remaining steps and parameters are the same as Example 1.

[0087] Example 4

[0088] In Example 4, except that the amount of the safety improver is 44.5 g and the amount of the low boiling point solvent is 33.5 g, which are different from Example 1, the other steps and parameters are the same as those of Example 1.

[0089] Example 5

[0090] In Example 5, except that the amount of the safety improver is 74 g and the amount of the low boiling point solvent is 196 g, which are different from Example 1, the other steps and parameters are the same as those of Example 1.

[0091] Example 6

[0092] In Example 6, except that 100g of polymer monomer is 40g of methyl acrylate plus 60g of acrylonitrile, and the low boiling point solvent is 1,1,1,2,3,3-hexafluoro-3-(2,2,3,3-tetrafluoropropoxy)propane, which is different from Example 1, the other steps and parameters are the same as Example 1.

[0093] Table 1

[0094]

[0095]

[0096] Thermal performance and rate performance tests were conducted on batteries using the composite microspheres of Examples 1 to 6, batteries without composite microspheres, and batteries using cyclosiloxane alone. Comparative Example 1 was used for batteries without composite microspheres, and Comparative Example 2 was used for batteries using cyclosiloxane alone.

[0097] The process of preparing a battery using the composite microspheres of Examples 1-6 is as follows:

[0098] Silicon-carbon material, composite microspheres of Examples 1-6, conductive carbon black, and polyacrylate lithium PAALi were mixed in a ratio of 85:5:5:5, deionized water was added, and the negative electrode was obtained by centrifugal homogenization, coating, and drying. The electrode was rolled and punched, and then mixed with metal lithium, a separator, and 1M LiPF 6 Ethylene carbonate EC / ethyl methyl carbonate EMC / fluoroethylene carbonate FEC (volume ratio of 20 / 70 / 10) electrolyte, assembled into 2032 button cells.

[0099] The process of preparing the battery without using composite microspheres is:

[0100] Silicon carbon material, conductive carbon black, and polyacrylate lithium PAALi were mixed in a ratio of 90:5:5, deionized water was added, and the negative electrode was obtained by centrifugal homogenization, coating, and drying. The electrode was rolled and punched, and then mixed with metal lithium, diaphragm, and 1M LiPF 6 EC / EMC / FEC (volume ratio is 20 / 70 / 10) electrolyte, assembled into 2032 button cells.

[0101] The process of preparing a battery using cyclosiloxane alone is as follows:

[0102] Silicon carbon material, conductive carbon black, and polyacrylate lithium PAALi were mixed in a ratio of 90:5:5, deionized water was added, and the negative electrode was obtained by centrifugal homogenization, coating, and drying. The electrode was rolled and punched, and then mixed with metal lithium, diaphragm, and 1M LiPF 6EC / EMC / FEC / 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane / 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (volume ratio of 20 / 70 / 10 / 2 / 8) electrolyte, assembled into 2032 button cells.

[0103] The thermal performance test process includes: inserting lithium into each of the batteries prepared above to 0.005V at a low current of 0.05C; then scraping the fully inserted powder and adding the above electrolyte to test the thermogravimetric analysis TG-differential scanning calorimetry DSC.

[0104] The rate performance test includes: inserting lithium into each of the batteries prepared above to 0.005V at a low current of 0.05C, aging at 45°C for 12h, and de-lithiation at 4C to 1.5V to test the discharge capacity retention rate.

[0105] The test results are shown in Table 2.

[0106] Table 2 Test results

[0107]

[0108] It can be seen from the data of Examples 1, 2 and 3 that as the content of methyl acrylate in the polymer monomer increases and the content of the crosslinking agent decreases, the strength of the obtained composite microspheres decreases, and the glass transition temperature decreases, and thus they are easier to break and generate less heat. However, too low strength can easily cause some composite microspheres to break during the battery manufacturing process, releasing internal safety improvement additives and low boiling point solvents, changing the electrolyte and SEI film components, and having a certain impact on the battery rate performance.

[0109] It can be seen from the data of Example 1, Example 4 and Example 5 that as the shell of the composite microspheres becomes thicker and the mass fraction of the low-boiling-point solvent and the thermoplastic polymer monomer is lower, the dispersibility of the safety improver and the low-boiling-point solvent becomes relatively poor, resulting in the composite microspheres with less low-boiling-point solvent being less likely to break and release, both of which lead to slightly poor effects on blocking the negative electrode and electrolyte, and relatively high heat generation. At the same time, the slightly thin shell is prone to partial rupture during the battery manufacturing process, affecting the battery rate performance.

[0110] It can be seen from the data of Example 1 and Example 6 that when the methyl acrylate content is low, the glass transition temperature of the thermoplastic polymer shell is high and the boiling point of the solvent is high, resulting in delayed shell rupture, a later effect of the safety improver, and higher heat generation.

[0111] It can be seen from the data of Example 1 and Comparative Example 1 that placing the safety improver in the microspheres can effectively avoid contact with the negative electrode during normal use and will not affect the rate performance of the battery.

[0112] It can be seen from the data of Example 1 and Comparative Example 2 that, although adding the safety improver directly into the electrolyte can inhibit the reaction between the negative electrode material and the electrolyte, it also greatly increases the negative electrode impedance, resulting in a serious reduction in rate performance.

[0113] The above results show that the addition of the composite microspheres of this embodiment can significantly reduce the heat generated by the reaction between the lithium-embedded negative electrode and the electrolyte while maintaining the battery rate performance. At the same time, the percentage of methyl acrylate in the polymer monomer and the content of the crosslinking agent both affect the strength and glass transition temperature of the composite microspheres.

[0114] In the description of this specification, the description with reference to the terms "one embodiment / method", "some embodiments / methods", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment / method or example are included in at least one embodiment / method or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment / method or example. Moreover, the specific features, structures, materials or characteristics described may be combined in a suitable manner in any one or more embodiments / methods or examples. In addition, those skilled in the art may combine and combine the different embodiments / methods or examples described in this specification and the features of the different embodiments / methods or examples, unless they are contradictory.

[0115] It should be noted that, in the present application, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "comprise one..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements. In the present application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically stipulated.

[0116] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A composite microsphere, characterized in that: It comprises a core and a shell, wherein the core comprises a safety improver and a low boiling point solvent having a boiling point not higher than 105°C, and the shell is prepared from a thermoplastic polymer monomer and a crosslinking agent; The safety improving agent is cyclosiloxane.

2. The composite microsphere according to claim 1, characterized in that: The safety improver includes at least one of 1,3,5-trimethyl-1,3,5-tris(3,3,3-trifluoropropyl)cyclotrisiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetra(3,3,3-trifluoropropyl)cyclotetrasiloxane, octamethylcyclotetrasiloxane, 2,2,4,4,6,6-hexamethylcyclotrisiloxane, and 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane.

3. The composite microsphere according to claim 1, characterized in that: The low boiling point solvent includes at least one of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,1,2,3,3-hexafluoro-3-(2,2,3,3-tetrafluoropropoxy)propane, 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether, and 1,1,2,3,3,3-pentafluoropropyl-2,2,2-trifluoroethyl ether.

4. The composite microsphere according to claim 1, characterized in that: The thermoplastic polymer monomer includes at least one of acrylonitrile, methyl methacrylate, methacrylic acid, methyl acrylate, butyl acrylate, vinyl acetate, and halogenated olefins.

5. The composite microsphere according to claim 4, characterized in that: The thermoplastic polymer monomers include methyl acrylate and other monomers; The mass of the methyl acrylate is not less than 60% of the total mass of the thermoplastic polymer monomer; The other monomer is one of acrylonitrile, methyl methacrylate, methacrylic acid, butyl acrylate, vinyl acetate, and halogenated olefins.

6. The composite microsphere according to claim 1, characterized in that: The crosslinking agent is 1,4-butanediol dimethyl acrylate or polydipentaerythritol hexaacrylate; The mass of the cross-linking agent is 0.05-1% of the mass of the thermoplastic polymer monomer.

7. The composite microsphere according to claim 1, characterized in that: The ratio of the mass of the safety improver and the low boiling point solvent to the mass of the thermoplastic polymer monomer is (0.78-2.7):1; The ratio of the mass of the safety improver to the mass sum of the low boiling point solvent and the thermoplastic polymer monomer is 1:(3-4).

8. The composite microsphere according to claim 1, characterized in that: The average particle size Dv(50) of the composite microspheres is between 5 and 30 μm.

9. A method for preparing the composite microspheres according to claim 1, characterized in that: It includes: Thermoplastic polymer monomers, initiators, crosslinking agents, safety improvers and low boiling point solvents are mixed and stirred to obtain an oil phase solution; Deionized water, a dispersant, sodium chloride, trisodium citrate and ethanol are mixed and stirred to obtain an aqueous phase solution; The aqueous phase solution and the oil phase solution are mixed and stirred to make the oil phase form uniform micron-sized droplets dispersed in the aqueous phase to obtain a suspension; The suspension is subjected to a cross-linking reaction under conditions of mechanical stirring and heating to obtain a mixture; After the mixture is cooled to room temperature, it is separated, washed and low-temperature dried to obtain the composite microspheres.

10. Use of the composite microsphere according to any one of claims 1 to 8 in a negative electrode of a battery.